COVID-19 and cardiovascular comorbidity: novel approaches to reduce mortality - S. S. Bunova; P. I. Okhotnikova; Yu. P. Skirdenko; N. A. Nikolaev; O. A. Osipova; N. I. zhernakova (Кардиоваскулярная терапия и профилактика)
Cardiovascular diseases (CVDs) remain the leading cause of death worldwide and significantly affect patient quality of life and socioeconomic status. Numerous reports consistently demonstrate that CVDs are a major risk factor for severe course of coronavirus disease 2019 (COVID-19), including higher risks of hospitalizations and inpatient mortality. In the context of the current pandemic, managing patients with CVDs requires special attention from doctors. There are now more and more reports of the long-term effects of COVID-19. The long-term effects on cardiovascular system of millions of COVID-19 survivors are currently unknown. The aim of the review was to systematize the accumulated knowledge about the mutual influence of COVID-19 and CVDs. The features of CVD impact on the course and outcomes of COVID-19, as well as the reasons for the worsening of CVD course in patients with COVID-19 are considered. The impact of redistribution of health care resources and large-scale isolation measures on the management of patients with CVDs is discussed. The review also presents the most relevant data on long COVID. Predictors of a long-term disease course were identified for risk stratification in order to timely implement preventive measures and develop an individualized treatment. The authors focused on finding novel approaches to reduce CVD mortality during a pandemic.